INFORMATION PAYROLL SYSTEM AT PT. INDONESIA AMDAH USING VISUAL BASIC 6.0 - David Muhammad Nur; Irfan Irfan, Skom, MMSi (Jurnal Sistem Informasi, 2009)
This scientific writing menj elaskanmengenai payroll system on PT. Amdah Indonesia that during this process is done manually. Therefore the writer create a computerized payroll system using the language of pemrogramanVisual Basic 6.0 and Databases using MS -Access. Hopefully this writing has become an alternative for a company or to its employees who expect all their activities are operating effectively, efficiently and coordinated.Â